Telehealth insulin titration in adults with diabetes: a randomized controlled trial comparing bluetooth-enabled versus traditional glucometers - Lian, Xia; Liew, Hui Ling; Lee, Ying Shan; Lin, Anita Ying; Goh, Eunice Yu Wen; Goh, Christina Yang Hoon; Quek, Hwee Chen; Tan, Isaac Jun Song; Lim, Helen; Chee, Ying Jie; Quek, Zhi Han; Shen, Liang; et al. (Frontiers in Endocrinology, 2025)
ObjectiveBlood glucose self-monitoring is crucial for individuals with diabetes mellitus and on insulin therapy to ensure safe glycemic control and optimal treatment outcomes. This study evaluates the effectiveness of Bluetooth-enabled glucometers (BTG) versus Traditional glucometers (TG) in a telehealth insulin titration program for individuals with diabetes.MethodsThis 24-week, open-label, randomized controlled trial enrolled 120 participants with diabetes from a tertiary hospital. Participants, aged 21–70 years, who required either insulin initiation or intensification were randomly assigned to either the BTG or TG group. Both groups received three biweekly teleconsultations with Diabetes Nurse Educators for insulin dose adjustments, followed by two clinic visits at three-month intervals.ResultsParticipants were predominantly male, Chinese, and diagnosed with Type 2 diabetes. Both groups demonstrated significant reductions in glycated hemoglobin (HbA1c) throughout the study. The TG group achieved HbA1c reductions of 2.8% at Week 12 and 3.1% at Week 24 (both p < 0.001), while the BTG group showed reductions of 2.23% and 2.18% respectively (both p < 0.001). There were no significant between-group differences in HbA1c at any time point. However, the BTG group showed significantly fewer emergency department visits than TG (4.1% vs. 16.7%, p = 0.039). Both groups demonstrated improvements in diabetes-related distress, with no significant differences between groups.ConclusionBTG did not demonstrate glycemic superiority over TG in telehealth insulin titration; however, its association with reduced emergency department visits suggests potential benefits for healthcare utilization. Future studies should investigate the integration of BTG with comprehensive diabetes care platforms, with a focus on long-term outcomes and cost-effectiveness.Clinical Trial Registrationhttps://www.isrctn.com/ISRCTN69173566, Identifier: ISRCTN69173566.